2021
DOI: 10.3389/fneur.2021.648702
|View full text |Cite
|
Sign up to set email alerts
|

Association of Trimethylamine N-Oxide and Its Precursor With Cerebral Small Vessel Imaging Markers

Abstract: Background: High plasma levels of trimethylamine N-oxide (TMAO) and its precursor choline have been linked to stroke; however, their association with cerebral small vessel disease remains unclear. Here we evaluated the association of plasma levels of TMAO and choline with imaging markers of cerebral small vessel disease, including white matter hyperintensities, lacunes, and cerebral microbleeds.Methods: We performed a baseline cross-sectional analysis of a multicenter hospital-based cohort study from 2015 to 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 50 publications
0
8
0
1
Order By: Relevance
“…Accumulating evidence has proven the causal links among TMAO, CAD, and stroke (Witkowski et al, 2020). Elevated TMAO and choline levels have recently been found to be associated with severe WMHs, especially P-WMH (Chen et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has proven the causal links among TMAO, CAD, and stroke (Witkowski et al, 2020). Elevated TMAO and choline levels have recently been found to be associated with severe WMHs, especially P-WMH (Chen et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“… 21 Similarly, another recent study which detected the relationships of trimethylamine N-oxide with PV-WMH and D-WMH in a large cohort of TIA/AIS patients found that elevated trimethylamine N-oxide levels were associated with a higher risk of WMH burden, and more closely associated with PV-WMH than D-WMH. 40 We speculate that the discrepancy may be attributed to anatomical, histological as well as pathophysiological differences between PV-WMH and D-WMH. Previous histopathological studies have demonstrated that PV-WMH contained more immunoreactive microglia and astrocytes than D-WMH.…”
Section: Discussionmentioning
confidence: 82%
“…We found that the WMH signal of SHR rats was significantly severe compared with age-matched WKY rats, and 35-week SHR rats developed stronger WMH signals than 24-week SHR rats, indicating that the development of hypertension promoted the severity of WML with age ( Figure 1B ). TMAO, a gut microbiota metabolite, is reported to be correlated with WMH in CSVD and the development of hypertension ( Liu et al, 2019 ; Chen et al, 2021 ). Hereon, we detected the change of TMAO concentration in SHR and WKY rats.…”
Section: Resultsmentioning
confidence: 99%
“…And we also found a slight increase of TMAO level in 35-week SHR in comparison with 24-week SHR and TMAO was positively involved in the decreased volumes of white matter, indicating that TMAO might be correlated with the development of WML. The increased TMAO level is strongly associated with the severity of WMH ( Chen et al, 2021 ). Govindarajulu et al (2020) reported that TMAO could enhance endoplasmic reticulum stress to induce impairment in synaptic plasticity, contributing to cognitive deficits in Alzheimer’s model and insulin resistance mouse.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation